Infectious pancreatic necrosis virus isolated from farmed rainbow trout and tilapia in Kenya is identical to European isolates. Issue 8 (28th May 2018) - Mulei, I R; Nyaga, P N; Mbuthia, P G; Waruiru, R M; Njagi, L W; Mwihia, E W; Gamil, A.A.A.; Evensen, Ø; Mutoloki, S
Abstract: Infectious pancreatic necrosis virus (IPNV) is an aquabirnavirus that causes serious diseases in a variety of fish species worldwide. It has been isolated from a large number of healthy fresh and marine water fish. Prior to this study, there was no record of the presence of IPNV infection in Kenya. Here, the presence of IPNV in farmed rainbow trout and tilapia was examined in Nyeri County of central Kenya. Head kidney samples taken from five rainbow trout and three tilapia farms and stored in RNALater ® were processed by PCR followed by sequencing of a segment A fragment covering nucleotide positions 2, 120–2, 343 bp. IPNV was detected in all the farms sampled with infection ratios ranging from 0.3 to 0.78 although the infections were not associated with any specific clinical signs of disease. These findings were supported by immunohistochemistry staining of the virus in the kidney and exocrine pancreas of rainbow trout. Sequence alignment and phylogenetic analysis revealed that the Kenyan isolates were identical to European isolates, suggesting a common origin. These findings highlight the need for better biosecurity procedures with more stringent surveillance programmes and control for fish diseases, especially focusing on imported breeding materials to Kenya.